News in a digital age comparing the presentation of news information over time and across media platforms - Kavanagh, Jennifer 1981-; Marcellino, William; Blake, Jonathan S.; Smith, Shawn; Davenport, Steven; Tebeka, Mahlet Gizaw (RAND, 2019)
This report presents a quantitative assessment of how the presentation of news has changed over the past 30 years and how it varies across platforms. Using RAND-Lex, a suite of tools that combine machine learning and text analysis, the researchers considered such linguistic characteristics as social attitude, sentiment, affect, subjectivity, and relation with authority for four comparisons: newspapers before and after 2000 (through 2017), broadcast television news before and after 2000 (through 2000), broadcast news and prime-time cable programming for the period from 2000 to 2017, and newspapers and online journalism during the 2012-2017 period. Over time, and as society moved from "old" to "new" media, news content has generally shifted from more-objective event- and context-based reporting to reporting that is more subjective, relies more heavily on argumentation and advocacy, and includes more emotional appeals. These changes were observed across platforms, appearing least significant in the evolution of print journalism and most stark in comparisons of broadcast news with prime-time cable programming and of print journalism with online journalism. The report quantifies the sizes of observed changes and provides examples of what these changes look like in context. It also includes a discussion of the implications of these trends for the changing media ecosystem and for Truth Decay-the term RAND uses to refer to the diminishing role of facts and analysis in political discourse
"Countering truth decay: a RAND initiative to restore the role of facts and analysis in public life."
Keywords: Geschichte 1990-2017; Massenmedien; Journalismus; Neue Medien; Berichterstattung; USA; Mass media / Objectivity / United States; Journalism / Objectivity / United States; Newspapers; Television broadcasting of news / United States; Digital media / United States; Digital media; Journalism / Objectivity; Mass media / Objectivity; Television broadcasting of news; United States